Energy-Saving Principles and Technologies for Induction Motors. - Ma, Wenzhong (John Wiley & Sons, Incorporated, 2017)
A unique guide to the integration of three-phase induction motors with the emphasis on conserving energy - The energy-saving principle and technology for induction motor is a new topic, and there are few books currently available; this book provides a guide to the technology and aims to bringabout significant advancement in research, and play an important role in improving the level of motor energy saving- Includes new and innovative topics such as a case study of energy saving in beam pumping system, and reactive compensation as a means of energy saving- The authors have worked in this area for 20 years and this book is the result of their accumulated research and expertise. It is unique in its integration of three-phase induction motors with the emphasis on conserving energy- Integrates the saving-energy principle, technology, and method of induction motors with on-site experiences, showing readers how to meet the practical needs and to apply the theory into practice. It also provides case studies and analysis which can help solve problems on-site.